The regulator of G-protein signalling protein mediates D-glucose-induced stomatal closure via triggering hydrogen peroxide and nitric oxide production in Arabidopsis - Hei, Shumei; Liu, Zhifeng; Huang, Aixia; She, Xiaoping (Functional plant biology : FPB, 2018)
2-Deoxy-D-glucose, 3-O-methyl-D-glucose and D-mannose are all non-metabolisable D-glucose analogues. Among these, 2-deoxy-D-glucose and D-mannose are substrates for hexokinase (HXK). D-sorbitol and D-mannitol are reduced forms of D-glucose and are typically used as comparable osmotic solutes. Similar to 2-deoxy-D-glucose and D-mannose, D-glucose induced stomatal closure in Arabidopsis, whereas 3-O-methyl-D-glucose, D-sorbitol and D-mannitol did not. The data show that the effect of D-glucose on stomata is metabolism-independent, HXK-dependent and irrelevant to osmotic stress. Additionally, the D-glucose induced closure of stomata in wild-type Arabidopsis, but did not in rgs1-1 and rgs1-2 or gpa1-3 and gpa1-4 mutants, indicating that the regulator of G-protein signalling protein (RGS1) and heterotrimeric guanine nucleotide-binding proteins (G proteins)-α subunit (Gα) also mediate the stomatal closure triggered by D-glucose. Furthermore, the effects of D-glucose on hydrogen peroxide (H2O2) or nitric oxide (NO) production and stomatal closure were more significant in AtrbohD or Nia2-1 mutants than in AtrbohF and AtrbohD/F or Nia1-2 and Nia2-5/Nia1-2. The data indicate that H2O2 sourced from AtrbohF and NO generated by Nia1 are essential for D-glucose-mediated stomatal closure. D-glucose-induced H2O2 and NO production in guard cells were completely abolished in rgs1-1 and rgs1-2, which suggests that RGS1 stimulates H2O2 and NO production in D-glucose-induced stomatal closure. Collectively, our data reveal that both HXK and RGS1 are required for D-glucose-mediated stomatal closure. In this context, D-glucose can be sensed by its receptor RGS1, thereby inducing AtrbohF-dependent H2O2 production and Nia1-catalysed NO accumulation, which in turn stimulates stomatal closure.